Environmental peacebuilding in Latin America and the Caribbean: Bridging gaps and harnessing opportunities - Higuera-Florez, Julian; Medina, Leonardo; Acuña-Alfaro, Jairo; De Francisco, Iñaki; Pacillo, Grazia; Madurga-Lopez, Ignacio (2024)
The goal of this brief is to reflect on the gaps, challenges and opportunities of environmental peacebuilding efforts in Latin America and the Caribbean (LAC). Specifically, it aims to demonstrate the importance of producing more comprehensive and robust evidence to bridge the gaps in understanding the interrelations between environmental management and peacebuilding opportunities in a LAC context. Additionally, it explores the opportunities and challenges of introducing environmental peacebuilding scientific evidence and approaches into policymaking, programming and investment in the region, with the goal of ensuring multisectoral engagement and ending siloed approaches among institutions working on climate action, environmental management, security, peacebuilding, and the triple nexus between humanitarian, development and peace (HDP).